PENGARUH KUALITAS PELAYANAN HARGA OBAT DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA APOTEK OLEAN FARMA (STUDI PADA APOTEK OLEAN FARMA TENGGIR BARAT KABUPATEN SITUBONDO) - Samsuri, Moh; Karnadi, Karnadi; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to analyze the effect of the variable influence of service quality, drug price and location on consumer buying interest at the Olean FarmaTenggir Barat Pharmacy, Situbondo Regency. Collection method. Service Quality Variable (X1) with a significant level of 5% obtained a tcount of 0.971 with a significant value of 0.334. From these results it can be said that the Service Quality variable (X1) has a positive but not significant effect because the results of the t-count have a value of 0.971. In addition, it is known that the t-count is 0.971 < t-table 1.985 and the significant value of t-count is 0.334, so Ho is accepted and Ha is rejected. This means that there is no partially positive significant effect of the Service Quality variable (X1) on the Consumer Purchase Order variable. Price variable (X2) with a significant level of 5% obtained t-count results of 2.515 with a significance of 0.014. It can be said that the price variable (X2) has a positive effect on the result of t-count which has a value of 2.515. In addition, it is known that t count 2.515 > t table 1.985 and significant t 0.014 < 0.050, then Ho is rejected and Ha is accepted. This means that the partially positive significant effect of the Price variable (X2) on the Consumer Buying Interest variable (Y) Apotek Olean FarmaTenggir Barat Situbondo Regency. Location variable (X3) with a significance level of 5% obtained t-count results of 7.240 with a significance value of 0.000, it can be said that the Location variable (X3) has a positive effect because the results of t-count which have a value of 7.240. In addition, it is known that t arithmetic 7.240 > t table 1.985 and significant value t 0.000 < 0, then Ho is rejected and Ha is accepted. This means that the partially positive significant effect of the Location variable (X3) on Consumer Buying Interest (Y) at the Olean FarmaTenggit Barat Pharmacy, Situbondo Regency.